Appearance Design Method of Smart Street Lamp Based on Kansei Engineering - Junchao Ge; Lipeng Wang (Advances in Multimedia)
In order to improve the scientificity of the appearance design of smart street lamps, this paper studies the appearance design method of smart street lamps combined with Kansei engineering so as to improve the appearance design effect of street lamps. Moreover, this paper optimizes the design of free-form surface optical light distribution, microlens array to improve the light extraction efficiency of high-power smart street lamps, and the heat dissipation structure of lamps. In addition, in view of the shortcoming that the direct design of free-form surface lenses for smart street lamps is not widely applicable, this paper proposes the concept of integration of microlens array packaging for smart street lamps. Finally, this paper verifies that the intelligent street lamp design based on Kansei engineering meets the lighting needs through experimental research. Through the experimental evaluation, it can be seen that the appearance design method of smart street lamps based on Kansei engineering proposed in this paper can effectively improve the structural performance of street lamps.